2018
DOI: 10.1177/0267658318791651
|View full text |Cite
|
Sign up to set email alerts
|

Input frequency and construction interference interactions in L2 development

Abstract: The interaction between input frequency and constructional interference receives little attention in second language (L2) research. Two studies were conducted to test the effect of this interaction. Study 1 examined effects of both Zipfian frequency (ZF) and balanced frequency (BF) on L2 learning of English subject-extracted relative clauses (SRs). Participants learned SRs and finished a picture description task at pretest, posttest and delayed posttest. Results suggest that ZF was not superior to BF for learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…One such factor pertains to frequency, which albeit being considered ubiquitous in L1 acquisition (Ambridge et al, 2015) the role it plays in L2 acquisition is not fully understood. For instance, Linford and colleagues (2017) found no independent effects of lexical frequency in the production of subject pronoun expression among non-native speakers of Spanish but Zhang and Dong (2019) report that token frequency predicted activation of L1 in the acquisition of subject relative clauses in English. Importantly, Davydova (2021) reports that cognitive salience is implicated in frequency effects in the replication of native like patterns of quotative like among L2 English speakers, with the implication being that frequency interacts with other factors in complex ways (Ellis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One such factor pertains to frequency, which albeit being considered ubiquitous in L1 acquisition (Ambridge et al, 2015) the role it plays in L2 acquisition is not fully understood. For instance, Linford and colleagues (2017) found no independent effects of lexical frequency in the production of subject pronoun expression among non-native speakers of Spanish but Zhang and Dong (2019) report that token frequency predicted activation of L1 in the acquisition of subject relative clauses in English. Importantly, Davydova (2021) reports that cognitive salience is implicated in frequency effects in the replication of native like patterns of quotative like among L2 English speakers, with the implication being that frequency interacts with other factors in complex ways (Ellis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has produced various findings on the effect of skewed input. While some studies found it to be advantageous (e.g., Casenhiser & Goldberg, 2005; Goldberg et al, 2007; Madlener, 2016; Zhang and Dong, 2019, study 2; Zhang & Mai, 2023, study 2), subsequent L2 studies reported either no advantage for skewed input (Nakamura, 2012; Year & Gordon, 2009; Zhang & Mai, 2023, study 1) or even an advantage for balanced input (Brooks et al, 2017; McDonough & Trofimovich, 2013; McDonough & Nekrasova-Becker, 2014; Zhang & Dong, study 1). In line with previous work that explored ATI in SLA (for a review, see, e.g., Vatz et al, 2013), this study explored the effect of individual WM capacity in modulating the effect of skewed and balanced input under inductive and deductive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found no major advantage for either skewed or balanced input in the acquisition of a new construction by FL learners. These studies cover a range of constructions and participants, such as prenominal adjective participles (Zhang & Dong, 2016) and relative clauses (Zhang & Dong, 2019) in teenaged Chinese learners of English, Russian morphology in U.S. college students (Brooks, Kwoka, & Kempe, 2017), and past counterfactuals (Révész, Sachs, & Hama, 2014) and Esperanto transitives (Fulga & McDonough, 2016) in ESL students. The tasks employed to examine the effect of input also vary, including grammaticality judgement (Zhang & Dong, 2016), written production (Zhang & Dong, 2019), forced‐choice comprehension (Fulga & McDonough, 2016; Révész et al., 2014), and oral production (Brooks et al., 2017; Révész et al., 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a few cases, FL learners even showed better performance with balanced input. FL researchers generally attribute the discrepant findings to FL learners’ explicit metalinguistic knowledge and their tendency to rely on explicit learning when processing FL‐like input (Fulga & McDonough, 2016; McDonough & Trofimovich, 2013; Nakamura, 2012; Year & Gordon, 2009; Zhang & Dong, 2019). In FL classrooms, instruction and learner attention are usually directed to formal correctness of expressions.…”
Section: Literature Reviewmentioning
confidence: 99%